Duodenal dieulafoy injury: case report - M. López, Juan D.; Hernández, Christian A. T.; Gómez, Darinel O.; Návar, Aarón D.; Ortiz, Carlos A. B.; Reséndiz, Benjamín F.; Azpera, Guadalupe L. L.; Delgado, Katia E. H. (International Surgery Journal, 2023)
Dieulafoy's lesion is a rare but important cause of upper or lower gastrointestinal bleeding, resulting from bleeding from a large arterial vessel. Its extragastric location is rare and the diagnosis is usually endoscopic, allowing simultaneous treatment either with injection of sclerosing substances or by mechanical means. We present the case of a 72-year-old woman with severe gastrointestinal bleeding with Dieulafoy's lesion in the duodenal bulb, successfully diagnosed and treated endoscopically.